Protecting Children's Rights through the Transformation of Employment Policies in South Sulawesi - Paikah, Nur; Yamin, Muhammad; Malik , Faissal; Nasution, Abdullah Akhyar; Chalid, Ibrahim (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
This study aims to analyze employment policies to protect children's rights in employment relationships in South Sulawesi as an effort to guarantee citizens' constitutional rights as stipulated in laws and regulations on employment. This study is an empirical legal study analyzed using human rights theory, child protection and corporate social responsibility theory. Data collection techniques used in-depth interviews and literature review. The findings reveal that labor policies aimed at safeguarding children remain inadequate, resulting in economic, social, and moral exploitation, as well as negative consequences for children’s education, health, and overall development. The absence of adequate protection in employment relations ultimately hinders the formation of high-quality human resources. To address this, stronger government intervention and oversight are essential, particularly through the effective empowerment of labor inspectors to enforce regulations. This study recommends the need for harmonization of the Human Rights Law, the Employment Law, and the Child Protection Law, as well as the establishment of an Independent Employment Oversight Committee involving academic experts. Such measures are necessary to ensure the effective implementation of labor protections, prevent the exploitation of children, and support Indonesia’s goal of cultivating superior human resources by 2045.